(untitled) (Baghdad Science Journal, 2022)
The products of composites material are very sesetive to many variables, such as manufacturing process, additive materials, …. etc. Filler or additive plays a major role to determine the formation of the properties and behavior of the composites. In this study, polyethylene terephthalate-based compounds were produced and characterized. The work is concerned to prepare samples of Polyethylene terephthalate (PET) - zinc-ferrite (ZnFe2O4) with different addition ratio as zinc-ferrite (1, 2, 5, 10, 15 and 20) wt% obtained from mixing the solution with a hot pressing method applied under optimum conditions. The densities of the composites for all samples were calculated. Through the work the diffusion of zinc-ferrite into the grain of Polyethylene terephthalate has been noted. Structural properties are studied by using X-ray powder pattern, the results of the XRD diffraction analysis showed that the structure for pure PET has four broad peaks at the (2θ=16.46°,17.45°, 22.72°,25.98°). The non-crystalline behavior of the polymer and the ceramic compound indicates the presence of a crystalline phase with a single cubic structure with a space group fd-3m (227)) (a=b=c=8.44 Å, V=601.45 (Å)³). While adding zinc-ferrite to PET in different concentrations to obtain (PET / ZnFe2O4) composites material will increase the intensity of the X-ray peaks, and change the location of the peaks with the addition of zinc-ferrite. It is noted that X-ray diffraction patterns for PET / ZnFe2O4 (20%) indicates that there was no apparent variation of the patterns of pure Zn-ferrite ceramic diffraction which showed that the crystalline structure remains stable in PET / ZnFe2O4. In addition, the electrical properties of the compounds represented by the dielectric constant (real and imaginary), dielectric loss ( tanδ) and the A.C conductivity as a function of a range of frequencies (50Hz-1MHz) have been measured. The results indicated that these properties increase with increasing concentrations of ceramic addition. On the other hand, these properties decrease with increasing frequency due to the change in polarization mechanisms. It has been proven that these prepared superposed materials possess good stability properties in a wide range of frequencies, making these polymeric overlays of wide use in many applications. As for the measurements of Shore D hardness, it has been shown that the hardness of the compounds increases with increasing ceramic concentrations.